Molecular level one-step activation of agar to activated carbon for high performance supercapacitors - Zhang, Lixing; Gu, Huazhi; Sun, Haibo; Cao, Feifei; Chen, Yao; Chen, George Zheng (Elsevier, 2018)
Activated carbon was synthesized by a simple one-step calcination of deoxygenated agar in a hot KOH aqueous solution, in which KOH plays both deoxidant and activation agent. The deoxygenation course omits high temperature carbonization in the conventional technology and leads to molecular level activation of agar in subsequent one-step calcination. The one-step activated carbon has superior specific surface area of 1672 m2 g−1 and total pore volume of 0.81 cm3 g−1. It also shows a maximum specific capacitance of 226 F g−1 in the KOH electrolyte, which is 1.4 times as high as that for the activated carbon by the conventional two-step method. This study provides potentially economical and effective means for the production of commercial activated carbon with high porosity for supercapacitors.